The First Report of Biallelic Missense Mutations in the SFRP4 Gene Causing Pyle Disease in Two Siblings - Sowińska-Seidler, Anna; Sztromwasser, Paweł; Zawadzka, Katarzyna; Sielski, Dawid; Bukowska-Olech, Ewelina; Zawadzki, Paweł; Kozłowski, Kazimierz; Jamsheer, Aleksander (Frontiers in Genetics, 2020)
Background: Pyle disease is a rare autosomal recessive bone dysplasia characterized by the broadening of metaphyses with generalized cortical thinning. Homozygous truncating mutations in secreted frizzled-related protein 4 (SFRP4) were, to date, the only known variants causative for this type of skeletal disorder. SFRP4 controls cortical and trabecular bone remodeling by differential regulation of the canonical and noncanonical WNT signaling in both bone compartments. Loss-of-function mutations in the SFRP4 gene lead to the protein deficiency causing skeletal phenotype typical for Pyle disease. Results: Herein, we report on the first SFRP4 missense mutations that occurred in compound heterozygosity in two siblings affected with Pyle disease, and which we have identified using a whole-genome sequencing approach followed by a comprehensive in-silico pathogenicity assessment. The variants we have found were extremely rare and evaluated to be disease-causing by several online available tools and software. Conclusion: With this paper, we have shown that Pyle disease may be related not only to SFRP4 truncating mutations but also to other loss-of-function alterations that possibly impair the protein capacity to bind WNT ligands. As we have expanded here, the range of deleterious variants underlying Pyle disease, we contribute to the knowledge on the pathogenesis of this rare skeletal disorder.